Pathological complete response of colorectal liver metastases following chemotherapy with S-1 and oxaliplatin (SOX) in combination with bevacizumab: A case report - YOKOTA, TOMOYA (D.A. Spandidos, 2011)
Pathological complete response to systemic chemotherapy is associated with more favorable survival in patients with colorectal cancer liver metastases. We present a case of a 63-year-old man with multiple liver metastases from descending colon cancer. Following surgical resection of the primary tumor, the patient received systemic chemotherapy with S-1 and oxaliplatin in combination with bevacizumab. On achievement of a markedly favorable response to chemotherapy, surgical treatment of liver metastases was performed, and the liver tumors were successfully resected without any macroscopic residue. Histopathological analyses showed necrotic tissue in the complete absence of residual viable tumor cells. This is the first reported case of a patient with multiple liver metastases from descending colorectal cancer to achieve a pathological complete response following systemic chemotherapy with S-1 and oxaliplatin in combination with bevacizumab. This regimen is a systemic chemotherapy option to ‘cure’ liver metastasis from colorectal cancer.